D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Moaddel, Ruin; Luckenbaugh, David A.; Xie, Ying; Villaseñor, Alma; Brutsche, Nancy E.; Machado-Vieira, Rodrigo; Ramamoorthy, Anuradha; Lorenzo, Maria Paz; Garcia, Antonia; Bernier, Michel; Torjman, Marc C.; Barbas, Coral; et al. (Psychopharmacology, 2015)
Rationale ( R,S )-ketamine is a rapid and effective antidepressant drug that produces a response in two thirds of patients with treatment-resistant depression (TRD). The underlying biochemical differences between a ( R,S )-ketamine responder (KET-R) and non-responder (KET-NR) have not been definitively identified but may involve serine metabolism. Objectives The aim of the study was to examine the relationship between baseline plasma concentrations of D-serine and its precursor L-serine and antidepressant response to ( R,S )-ketamine in TRD patients. Methods Plasma samples were obtained from 21 TRD patients at baseline, 60 min before initiation of the ( R,S )-ketamine infusion. Patients were classified as KET-Rs ( n = 8) or KET-NRs ( n = 13) based upon the difference in Montgomery–Åsberg Depression Rating Scale (MADRS) scores at baseline and 230 min after infusion, with response defined as a ≥50 % decrease in MADRS score. The plasma concentrations of D-serine and L-serine were determined using liquid chromatography-mass spectrometry. Results Baseline D-serine plasma concentrations were significantly lower in KET-Rs (3.02 ± 0.21 μM) than in KET-NRs (4.68 ± 0.81 μM), p < 0.001. A significant relationship between baseline D-serine plasma concentrations and percent change in MADRS at 230 min was determined using a Pearson correlation, r = 0.77, p < 0.001, with baseline D-serine explaining 60 % of the variance in ( R,S )-ketamine response. The baseline concentrations of L-serine (L-Ser) in KET-Rs were also significantly lower than those measured in KET-NRs (66.2 ± 9.6 μM vs 242.9 ± 5.6 μM, respectively; p < 0.0001). Conclusions The results demonstrate that the baseline D-serine plasma concentrations were significantly lower in KET-Rs than in KET-NRs and suggest that this variable can be used to predict an antidepressant response following ( R,S )-ketamine administration.